Travel and the British country house : cultures, critiques and consumption in the long eighteenth century - Stobart, Jon, 1966- (Manchester University Press, 2017)
Provides readers with fresh insights into the country house and the ways it was shaped by domestic and foreign travel. It brings famous and less familiar houses to life through the aspirations and acquisitions of owners; the admiring or caustic comments of visitors, and the constant flows of goods, people and ideas.